Comparison Between the GCS And the ‘Full Outline of UnResponsiveness’ Score in Predicting 30-Day Mortality in Patients with Impaired Consciousness Due to Stroke - Chowdhury, Mohammad Anwarul Azim; Md. Hassanuzzaman; Pradip Kumar Kayasthagir; Shiuly Majumder; Muhammed Syedul Alam; Mohammad Kawser Uddin Shouaibe; Md. Rubel; Syed Arif Uddin; Md. Shawkat Emran; Md. Khalequzzaman Linckon (Bangladesh Journal of Neuroscience, 2026)
Background: The Full Outline of UnResponsiveness (FOUR) score was introduced to overcome the limitations of the widely used Glasgow Coma Scale (GCS). Objective: The aim of the study was to evaluate the predictive ability of the GCS versus the FOUR score on 30-day mortality in patients with impaired consciousness due to stroke. Materials and methods: This prospective observational study was carried out among stroke patients with impaired consciousness admitted to the Department of Neurology of Chattogram Medical College & Hospital. A total of one hundred and thirty-two patients with evidence of stroke on computed tomography of the head were included. GCS and FOUR scores were assessed after enrollment in the study. The primary outcome measure was 30-day mortality after onset of stroke. A total of 128 patients were finally analyzed. Results: Mean (±SD) age was 62.6 (±11.5) years, and 54.7% were male. The types of stroke constituted ischemic, hemorrhagic, and subarachnoid hemorrhage in a proportion of 48.4%, 45.3%, and 6.3%, respectively. The mean (range) GCS score was 6.78 (3.0-10.0) and FOUR score was 9.72 (2-13). The 30-day mortality rate was 54.7%. In terms of predictive power for 30-day mortality, the area under the receiver operating characteristic curve (AUROC) (95% CI) for the GCS was 0.756 (0.673-0.838), and for the FOUR score was 0.909 (0.858-0.961). The difference in the AUROC values between the two coma scale scores (0.153) was statistically significant (p= 0.002, by Z test). With a cutoff score of 10.5, the FOUR score predicted 30-day mortality with a sensitivity and specificity of 93.1% and 81.4% respectively. For GCS, a cutoff score 6.5 had a sensitivity of 91.4% and 52.9% specificity. Subjects with the FOUR score of 2-11 had an 8.02-fold higher hazard of 30-day mortality (HR 8.02, 95% CI 3.21-20.04) compared to those with the score of 12 and above. Those with a GCS score of 3-7 had a 4.88-fold higher hazard of 30-day mortality (HR 4.88, 95% CI 2.97-8.03) compared to those with a score of 8 and above. Conclusion: Our study revealed FOUR score was significantly better than GCS inm predicting 30-day mortality in patients with impaired consciousness due to stroke.